Cultural and philosophical origins and attitudes of the early works of P. Tychyna: "The Last Supper, guillotine days" - H. V. Vdovychenko (Ukrainian Cultural Studies, 2020)
The article explores cultural and philosophical origins and attitudes of the early works of P. Tychyna, namely defining the ones events and phenomena of domestic and foreign ethnocultural and professional cultural life, cultural and philosophical ideas and teachings, as well as P. Tychyna’s own cultural and philosophical views, revealed mainly in his poetry books of 1918 – 1924. One of the most important, but still little- known pages of the biography and ideological and artistic evolution of P. Tychyna is the formation during the first third of the twentieth century, fundamental for his entire life cultural and philosophical guidelines of early creativity. The study of this problem is closely connected with the long overdue need for unbiased systematic classification and consideration of the whole spectrum of cultural and philosophical sources and guidelines of ideological and artistic evolution of the poet of ideologically contradictory poems-myths of Ukrainian national renaissance and enslavement – "Golden Homin" as a sacred figure-symbol of modernism and, at the same time, social realism in Ukrainian literature, the most famous and, at the same time, the most criticized domestic artist-model of evaluative polarity of official and public myth-making in the USSR and, later, in Ukraine. In light of the assessment of the main achievements of tychynology, a cultural-philosophical-literary analysis of the three stages of the ideological and artistic evolution of P. Tychyna of this period was carried out. These stages are: 1. formation (Kyiv-Chernyhiv): 1906 – 1916; 2. creative rise and blossoming (Kyiv): 1917 – 1921; 3. decline and crisis (Kyiv-Kharkiv): 1922 – 1929. Two groups of origins of the poet’s early works were examined. The first one is represented by domestic and foreign ethnocultures and consists of three subgroups of folklore: 1. Ukrainian; 2. foreign (of other Slavic peoples); 3. foreign, mainly of the peoples of the Near and Middle East (Armenian, Turkish and Indian). The second group is represented by domestic and foreign professional cultures, the last of which is divided into three subgroups: 1. Russian; 2. European and North American; 3. Eastern (the Near, Middle and Far East). P. Tychyna was a symbol and myth of modernism and Socialist realism in the literature and culture of the Ukrainian SSR, and the early stages of his cultural and philosophical credo’s evolution from the neopagan-Christian Ukrainian national-patriotic myth to the national-communist pantheistic-materialistic cosmogony.